2017
DOI: 10.1158/1078-0432.ccr-17-0478
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Primary Drug Resistance in FGFR1-Amplified Lung Cancer

Abstract: Purpose: The 8p12-p11 locus is frequently amplified in squamous cell lung cancer (SQLC); the receptor tyrosine kinase fibroblast growth factor receptor 1 (FGFR1) being one of the most prominent targets of this amplification. Thus, small molecules inhibiting FGFRs have been employed to treat FGFR1-amplified SQLC. However, only about 11% of such FGFR1-amplified tumors respond to single-agent FGFR inhibition and several tumors exhibited insufficient tumor shrinkage, compatible with the existence of drug-resistant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…109 In addition, treatment with FGFR inhibitors restored the sensitivity to EGFR-TKIs in primary drug-resistant SCLC cells. 110 Therefore, FGFR activation is one of the possible causes of developed resistance to EGFR-TKIs in lung cancer patients. and sensitivity to gefitinib and erlotinib were restored in clones derived from PC-9/GEF1-1 and PC-9/GEF2-1.…”
Section: Fibroblast Growth Factor Receptor Signalingmentioning
confidence: 99%
“…109 In addition, treatment with FGFR inhibitors restored the sensitivity to EGFR-TKIs in primary drug-resistant SCLC cells. 110 Therefore, FGFR activation is one of the possible causes of developed resistance to EGFR-TKIs in lung cancer patients. and sensitivity to gefitinib and erlotinib were restored in clones derived from PC-9/GEF1-1 and PC-9/GEF2-1.…”
Section: Fibroblast Growth Factor Receptor Signalingmentioning
confidence: 99%
“…Bypass signaling can also occur due to changes within the PI3K/AKT/mTOR [55][56][57] , MAPK [50,58,59] , STAT3 [60] and GSK3β [61] signaling pathways. Increased PI3K/AKT/mTOR signaling, independent of changes in upstream receptor tyrosine kinases has been described in DMS114 lung cancer cells (FGFR1 amplified) and RT112 urothelial cancer cells (FGFR3-TACC3) following chronic treatment with infigratinib [56] .…”
Section: Activation Of Intracellular Signaling Pathwaysmentioning
confidence: 99%
“…Although one report showed that NRAS and c-Met account for resistance in NCI-H1581 cells and treated these changes as a primary resistance mechanism, we did not observe similar results here. In addition, in contrast to our gradient of inhibitor concentrations, this report used long exposure times to obtain resistant clones, which we believed still reflected acquired rather than primary resistance responses (32).…”
Section: Discussionmentioning
confidence: 95%